Responses to novelty in wild insular birds: comparing breeding populations in ecologically contrasting habitats - Samara Danel; Nancy Rebout; Léna Bureau; Timothée Zidat; Dora Biro; Francesco Bonadonna (Animal Cognition)
Abstract Islands have always provided ideal natural laboratories for assessing ecological parameters influencing behaviour. One hypothesis that lends itself well to testing in island habitats suggests that animals frequenting highly variable environments should be motivated to approach and interact with (i.e. explore) novelty. Intra-species comparisons of populations living in ecologically different island habitats may, thus, help reveal the factors that modulate animals’ responses to novelty. In this study, we presented novel objects to two geographically isolated breeding populations of the black-faced sheathbill (Chionis minor), a sedentary land-based bird that frequents remote sub-Antarctic islands. In the first population (Chionis minor ssp. crozettensis), the “Crozet group” (Baie du Marin, Ile de la Possession, Crozet Islands), breeding pairs inhabit a variable habitat close to penguin (Aptenodytes patagonicus) colonies. In the second population (Chionis minor ssp. minor), the “Kerguelen group” (île Verte, Morbihan gulf, Kerguelen Islands) breeding pairs live in penguin-free territories. In this latter population, the environment is less variable due to the presence of a broad intertidal zone which ensures year-round food availability. At both Kerguelen and Crozet, at least one breeding partner in all pairs approached at least one of the novel objects, and we found no significant differences in the latency of approach between the two populations. However, sheathbills at Crozet touched objects significantly more than birds at Kerguelen, and were also faster to touch them. We discuss how environmental variability, along with other potential influencing factors, may favour exploration of novelty in this wild insular bird.